2013
DOI: 10.1021/am3026294
|View full text |Cite
|
Sign up to set email alerts
|

High Electrochemical Performance of Monodisperse NiCo2O4Mesoporous Microspheres as an Anode Material for Li-Ion Batteries

Abstract: Binary metal oxides have been regarded as ideal and potential anode materials, which can ameliorate and offset the electrochemical performance of the single metal oxides, such as reversible capacity, structural stability and electronic conductivity. In this work, monodisperse NiCo(2)O(4) mesoporous microspheres are fabricated by a facile solvothermal method followed by pyrolysis of the Ni(0.33)Co(0.67)CO(3) precursor. The Brunauer-Emmett-Teller (BET) surface area of NiCo(2)O(4) mesoporous microspheres is deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
529
7
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 729 publications
(583 citation statements)
references
References 47 publications
41
529
7
6
Order By: Relevance
“…In contrast to the carbonate precursor reported in previous work, [12][13][14][15][16]18 the MnCo-glycolate could yield a large weight loss due to the presence of a large amount of organic species by heating under atmosphere, the progress of which well controlled the different types of interiors. As commonly observed, the TEM and FESEM images in Fig.…”
Section: Lettercontrasting
confidence: 71%
“…In contrast to the carbonate precursor reported in previous work, [12][13][14][15][16]18 the MnCo-glycolate could yield a large weight loss due to the presence of a large amount of organic species by heating under atmosphere, the progress of which well controlled the different types of interiors. As commonly observed, the TEM and FESEM images in Fig.…”
Section: Lettercontrasting
confidence: 71%
“…This phenomenon is generally attributed to the reversible formation of a polymeric gel-like fi lm originating from kinetic activation in the electrode. [ 15,[46][47][48] More impressively, the discharge capacity of the ZZFO remains relatively stable after continuously cycling for ≈100 times, and is even kept as high as ≈837 mAh g −1 over 200 cycles. As seen from the FESEM and TEM images of the ZZFO anode after 200 cycles at the current rate of 1000 mA g −1 , some SMCs still can be evident (see Figure S11, Supporting Information), suggesting its desirable structural stability over cycling, which should be well responsible for the excellent cycling performance.…”
Section: Electrochemical Performance Of Hierarchical Mesoporous Zzfo mentioning
confidence: 94%
“…Compared with these materials, the ternary spinel oxide NiCo 2 O 4 has aroused much interest for use as an electrocatalyst for Li-O 2 batteries thanks to its good electronic conductivity and catalytic activity. [115,116] So far, various kinds of NiCo 2 O 4 -based electrocatalyst are reported, [117][118][119][120][121][122] including hierarchical NiCo 2 O 4 nanorods, [117] hierarchical macroporous/ mesoporous NiCo 2 O 4 nanosheets, [118] have been reported. As a typical example among these researches, Gong et al has reported a high-loading NiCo 2 O 4 nanoparticles (NCONP) anchored on three-dimensional N-doped graphene as an efficient bifunctional catalyst for Li-O 2 battery.…”
Section: Noble Metal Metal Oxides and Other Electrocatalystsmentioning
confidence: 99%